(untitled) (Mustansiria Dental Journal, 2025)
Aim: This study examined the cytotoxic effects of Nano Polyvinylidene-Fluoride (PVDF) on Human Gingival Fibroblasts (HGF) cells in comparison to sodium fluoride (NaF) varnish. Method: The MTT-Assay was performed to evaluate the cytotoxicity of the tested materials on HGFs. To assess the toxic effects, cell viability after the application of NaF varnish (2.26%) and PVDF (1.26%, 2.26%, and 3.26%) at each concentration.Results: The findings indicated that all concentrations of PVDF exhibited lower cytotoxicity compared to NaF varnish. Within the PVDF groups, the 3.26% concentration demonstrated the least cytotoxicity, succeeded by 2.26% and 1.26% respectively. On the other hand, NaF varnish exhibited the greatest toxicity among the evaluated substances.Conclusion: This innovative study demonstrates that Nano-PVDF, particularly at a concentration of 3.26%, is a promising material exhibiting enhanced biocompatibility and less cytotoxicity relative to traditional NaF varnish. All data represented that Nano-PVDF may function as a safer option in dental treatments, with exhibiting little adverse effects on oral cells.